The Influence of Quality Service and Citra on Satisfaction and Loyalty Community (The Empirical Study in Kecamatan Bulu, Sukoharjo) - Wibowo, Widyanto Setya (STIE AUB Surakarta)
This research has the aim to test the impact of service quality and image of public satisfaction and loyalty at Kantor Kecamatan Bulu, Sukoharjo. The analysis technique used is to use the instrument test, linearity test, regression analysis, path analysis, t test, F test, test the coefficient of determination and correlation analysis. Service quality and significant positive effect on satisfaction. Image positive and significant impact on satisfaction. Service quality, image and satisfaction of positive and significant effect on loyalty. F-test results can be concluded jointly variable service quality, image and satisfaction have a significant effect on loyalty. R2 results can be interpreted totaling 0.882 variation loyalty explained by the variable quality of service, image and satisfaction of 88.2% and 11.8% is explained by other variables outside the model study. Direct and indirect influence is the direct effect of service quality on loyalty produces a value higher than the indirect effect, so more effectively through direct. The direct effect on the image of loyalty produces a value higher than the indirect effect, so it is more effective through a direct path.Keywords: quality of service, image, satisfaction, loyalty